Numerical Simulation of 3D- Flow Structure and Heat Transfer for Longitudinal Riblet Upstream of Leading Edge Endwall Junction of Nozzle Guide Vane (Journal of Engineering, 2014)
The simulation have been made for  3D flow structure and heat  transfer with and withoutlongitudinal riblet upstream of leading edge vane endwall junction of first stage nozzle guide vane .The research explores concept of weakening the secondary flows and reducing their harmful effects.Numerical investigation involved examination of the secondary flows ,velocity and heat transfer rates by solving the governing equations (continuity, Navier -stokes and energy equations ) using the known package FLUENT version (12.1).The governing equations were solved for three dimentional, turbulent flowe, incompressible with an appropriate turbulent model (k-ω,SST) .The numerical solution was carried out for 25 models of V-groove riblet with wide ranges of height (h) and space (s). The results indicated that, the riblet endwall junction was a powerful tool for controlling the flow structure, reducing secondary flow formation,and elimination the effect of heat transfer at leading edg and passage . The drag reduction produced by riblet was proportional with their height and space. V-groove riblet with dimension of (h=1.35mm and s=2.26mm) was found to be the most effective in reduction of drag (2.7%) and heat transfer (21%) so it was selected as an optimum dimension of riblet model. The results also showed that the drag reduction produced by riblet was proportional to their size. The riblet model had a great effect in elimination spanwise ,pitchwise velocities ,but strength the streamwise velocity .At leading edge ,the effect of secondary flow was extended up to 23% from span height and 35% upstream leading edge .The riblet model caused an increase in momentom at a region very close to leading edge and to move stagnation point very close to the leading edge.